2016
DOI: 10.4172/jbb.1000272
|View full text |Cite
|
Sign up to set email alerts
|

Degradation in Pharmaceutical Creams: Ascorbic Acid Demonstrating Phenomenon: A Review

Abstract: This review is compilation of studies performed on stability and degradation of Ascorbic acid (AA) creams by keeping goal in mind to finely demonstrate the central premise of this article that is to cover all aspects related to degradation in pharmaceutical creams. It was required to deep insight into degradation specifically in pharmaceutical creams, influences for phenomenon, degradation products, stability concerns and its effects on efficacy and safety of pharmaceutical creams. Method: A literature survey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
1
0
1
Order By: Relevance
“…Vitamin C, or ascorbic acid, is an essential dietary nutrient and one of the naturally occurring antioxidants in nature [219,220]. It has been shown that vitamin C is capable of repairing DNA, alleviating oxidative stress, and modulating the activity of telomeres in the aging process, thereby eventually leading to longevity [221].…”
Section: Water-soluble Vitaminsmentioning
confidence: 99%
“…Vitamin C, or ascorbic acid, is an essential dietary nutrient and one of the naturally occurring antioxidants in nature [219,220]. It has been shown that vitamin C is capable of repairing DNA, alleviating oxidative stress, and modulating the activity of telomeres in the aging process, thereby eventually leading to longevity [221].…”
Section: Water-soluble Vitaminsmentioning
confidence: 99%
“…O ácido 2,3 dicetogulônico e o furfural são compostos finais de degradação do AA e intermediários de furona, que ocasionam à formação de pigmentos dourado ao marrom; produção de odores estranhos, que diminuem a qualidade geral do produto no qual o AA está inserido e forma dióxido de carbono (CO2) que, quando liberado, confere aspecto aerado ao produto (JUTJUS et al, 2015;MAIA, 2002). Assim, a formulação cosmética pode apresentar comportamento complexo, como a formação de produtos de degradação que podem ser tóxicos ou não, quebra das bases dos cremes, instabilidade física e química (NAVEED et al, 2016;MAIA, 2002), tornando as preparações inadequadas para o uso.…”
Section: Análise Organolépticaunclassified